Effect of omentin-1 on cancer stem cell surface markers and tumor-suppressive miRNA expression in a high-glucose environment associated with colorectal cancer - Lele Hou; Murong Xu; Xiaotong Zhao; Mingwei Chen; Cancan Hui; Hua Ji; Datong Deng (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate how omentin-1 impacts colorectal cancer stem cell surface markers and the expression levels of tumour-suppressive micro ribonucleic acid in a colorectal cancer-associated high-glucose environment. —Continue